2006
DOI: 10.1016/j.nurx.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the treatment of depression

Abstract: Summary: Depression is a highly prevalent and disabling condition associated with significant morbidity and mortality. Currently available treatments for depression include tricyclic antidepressants, monoamine oxidase inhibitors, selective serotonin reuptake inhibitors, serotonin norepinephrine reuptake inhibitors, various atypical antidepressants, and electroconvulsive therapy. Although these treatments are effective, a significant number of patients do not respond or achieve sustained remission despite aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 189 publications
(112 reference statements)
0
58
0
2
Order By: Relevance
“…In the ADAM (2) series of compounds, we have recently prepared two derivatives, the O-bridged, OADAM (3) and C-bridged, 4, and measured the kinetics of the brain uptake of the 125 I labeled compounds in rats [44] (Table 1). The specific hypothalamus uptake of C-bridged, [ 125 I]4, was inferior to that of OADAM (3) and ADAM (2). It was found that OADAM (3) consistently displayed a higher uptake in the hypothalamus (between 60-240 minutes post iv injection) than that of ADAM (2).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the ADAM (2) series of compounds, we have recently prepared two derivatives, the O-bridged, OADAM (3) and C-bridged, 4, and measured the kinetics of the brain uptake of the 125 I labeled compounds in rats [44] (Table 1). The specific hypothalamus uptake of C-bridged, [ 125 I]4, was inferior to that of OADAM (3) and ADAM (2). It was found that OADAM (3) consistently displayed a higher uptake in the hypothalamus (between 60-240 minutes post iv injection) than that of ADAM (2).…”
Section: Introductionmentioning
confidence: 96%
“…The specific hypothalamus uptake of C-bridged, [ 125 I]4, was inferior to that of OADAM (3) and ADAM (2). It was found that OADAM (3) consistently displayed a higher uptake in the hypothalamus (between 60-240 minutes post iv injection) than that of ADAM (2). The specific uptake of OADAM (3) in the hypothalamus exhibited the highest target to non-target ratio (hypothalamus/cerebellum, HY/CB, was 5.3 at 240 minutes post iv injection).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations